2019
DOI: 10.21608/pssjn.2019.66511
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Educational Program about Iron Chelation Therapy on the Quality of Life for Thalassemic Children

Abstract: Background: Thalassemia is the most common genetic disorder in Egypt, It is measured a fetal disease if proper chelation treatment is not established. The introduction of chelating agents able to removing extreme iron from the body has noticeably increased life expectancy time and improving the in general quality of life. the study aimed to identify the impact of an educational program about iron chelation therapy on the QoL for thalassemic children.Quasi-experimental research design was used , a convenient sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
(3 reference statements)
1
2
0
Order By: Relevance
“…Previously, this result comes in accordance with thatArmeli et al, (23) found that B-thalassemia education program in Italy appear to have dramatically increased awareness of the disorder. Recently, this finding was in agreement withZaghamir et al (24) reported that there was statistically significant improvement of children's knowledge. Subsequently, statistically significant improvement of children's quality of life at follow up compared with pre-intervention phase.…”
Section: Discussionsupporting
confidence: 91%
“…Previously, this result comes in accordance with thatArmeli et al, (23) found that B-thalassemia education program in Italy appear to have dramatically increased awareness of the disorder. Recently, this finding was in agreement withZaghamir et al (24) reported that there was statistically significant improvement of children's knowledge. Subsequently, statistically significant improvement of children's quality of life at follow up compared with pre-intervention phase.…”
Section: Discussionsupporting
confidence: 91%
“…They reported that educational counseling programs improved the quality of life of patients with thalassemia. In the same context, the study was consistent with El-Said Zaghamir al., (2019) in their study about "Impact of Educational Program about Iron Chelation Therapy on the Quality of Life for Thalassemic Children". This study revealed that there were statistically significant improvement of children's quality of life at follow up compared with pre-intervention phase.…”
Section: Effect Of Self -Determination Theory Based Intervention On Q...supporting
confidence: 90%
“… (Dehnoalian et al 2017) [ 46 ] Quality of life Iran Quasi-experiment 20 children age 15 to 30 years (mean= 23.06 ± 10.87) Educational Counseling Program Sf-36 Quality of Life Questionnaire Educational counseling programs are proven to improve the quality of life of children with thalassemia Mean ± SD Pre-test= 54.43 ± 5.60 Mean ± SD Post-test= 78.11 ± 17.64 P value= 0.002 10. (El-Said Zaghamir et al 2019) [ 47 ] Quality of life Iran Quasi-experiment 50 children aged 8–18 years (mean= 12.6±3.0) Educational Program about Iron Chelation Therapy Pediatric Quality of Life Inventory Tool The quality of life of children with thalassemia has significantly improved after being given the Educational Program about Iron Chelation intervention Mean Pre-test= 61 Mean Post-test= 76 P value<0.001 …”
Section: Resultsmentioning
confidence: 99%
“…Another educational program is an educational program about iron chelation therapy with a duration of 45–60 minutes. 47 Participants were explained about program objectives, content, and procedures. The method given in education is through group discussions and presentations of the results of the discussions.…”
Section: Resultsmentioning
confidence: 99%